Possible method for evaluation of virus, bacteria and yeasts infectivity by optical measurements - Rusinchuk, N.M.; Lozovski, V.Z.; Shydlovska, O.A.; Zholobak, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The possible method for evaluation of virus, bacteria and yeasts infectivity based on study of their absorption spectra has been proposed. The decrease in the samples infectivity was caused by adding the CeO₂ nanoparticles. Optical absorption of the samples was measured for the wavelength range from 400 to 750 nm. The obtained data detect the specific changes in absorption of the samples, which can be used for development of the new technique of evaluation of virus, bacteria and yeasts infectivity.